A Comprehensive Study of Bone Manifestations in Adult Gaucher Disease Type 1 Patients in Argentina - Oliveri, Beatriz (2019)
Gaucher disease (GD) is the most prevalent lysosomal storage disease, and bone involvement is the most disabling condition. The aim of the present study was to evaluate bone involvement in adult patients with GD, using an observational cross-sectional study. Patients were evaluated using X-rays, bone densitometry (BMD), trabecular bone score (TBS), magnetic resonance imaging (MRI), and biochemical bone markers. Thirty-two type 1GD patients were included (mean age: 40 ± 16 years). Patients had received velaglucerase for 2.7 ± 1.4 years; 19/32 had been treated previously with imiglucerase. Ninety-four percent of subjects met therapeutic goals for hematological parameters, and eight were splenectomized (SPX). Nineteen patients had irreversible bone lesions (IL), i.e., avascular necrosis, bone infarction, and/or vertebral fractures. MRI showed marrow infiltration in 71% of patients. Patients with IL had higher bone marrow burden than those without (p = 0.001). All SPX patients had IL, a higher prevalence of bone marrow edema (p = 0.02), and lower TBS (p = 0.03) than non-SPX patients. Only 18.7% of patients had abnormal BMD, with no correlation with fractures (FX). TBS values were < 1350 in 53% of patients and tended to be lower in those with FX (p = 0.06). Patients with P1NP in the lower quartile had lower TBS (p = 0.03) than those with P1NP in the higher quartiles. TBS correlated moderately but not significantly with P1NP (r = 0.32) and BMB (r = − 0.44). A high prevalence of IL was documented. Bone quality was more affected than BMD in fracture patients. Low bone formation, active bone marrow infiltration, and splenectomy might be implicated in IL.